Records Management and Job Performance of Non-Academic Staff in Osun State Tertiary Institutions - Akinola , Shalom Felicia; Alonge, Ayodele John (Communicate: Journal of Library and Information Science, 2023)
This study investigated the influence of records management on job performance of Non-academic staff in Osun State Tertiary Institution. The study adopted a descriptive and cross-sectional survey design. The population of the study was 2,861 non-academic staff of Osun State tertiary institutions. The sample size for this study was 338 non-academic staff of the institutions. The sample size was determined by Krejcie and Morgan sampling technique. The study adopted a structured questionnaire. Validity of the instrument was done by the supervisor and other experts in the field. The reliability test of the questionnaire yielded Cronbach’s Alpha value of 0.710. 338 questionnaires was administered and 252 was recovered which represent 75% response rate. Data were analysed using frequency counts and percentages to answer research questions and hypotheses were tested using correlation statistics of SPSS package at 0.05 level of significance. The study found significant correlation (R=0.657,p<0.05) between records management and job performance of non-academic staff.This study concluded that RM significantly influences JP of non-academic staff. The study recommended that the management of the institutions should consistently invest more on modern office equipment to enhance job performance of the non-academic staff.